Spatial evolution and mechanism of influence of the transition from old to new economic drivers in resource-based cities - YAN Mingtao, LI Jiangsu, YAN Mingyue (Ziyuan Kexue)
[Objective] To scientifically assess the level of transition from old to new economic drivers (TONED) in resource-based cities, it is essential to analyze the spatial evolution of the TONED and its underlying mechanisms. These would provide both theoretical and practical foundations for the green transition of resource-based cities. [Methods] This study comprehensively applied geospatial analysis techniques and Markov chains to study the spatial evolution characteristics of the TONED in 109 resource-based cities in China from 2011 to 2021, and analyzed the mechanism of influence of the TONED in terms of internal factors and external factors by applying obstacle models, optimal parameter geodetectors, and spatiotemporal geographically-weighted regression methods. [Results] First, the average index of the TONED in resource-based cities increased from 0.115 to 0.153, indicating a positive trend. Spatially, the TONED showed a pattern of high in coastal regions and low inland, with a reduction in spatial clustering effects. Second, neighboring areas played a significant role in the TONED, with observable path dependence. Third, internally, the primary barrier to the TONED was the changes in development methods. Key obstacles to the TONED include capital productivity, percentage of utilized foreign capital, labor productivity, and number of invention patents. Externally, factors such as city size, topography, temperature, and industrial scale played a dominant role in influencing the TONED, and had spatial differentiation characteristics. The interaction between factors exhibited characteristics of nonlinear enhancement and dual-factor reinforcement. Finally, heterogeneity analysis indicated that the percentage of utilized foreign capital was a major barrier to the TONED in growing and regenerative resource-based cities, while capital productivity hindered the TONED in mature and declining cities. City size primarily drove the TONED in mature and growing cities, temperature in declining cities, and topography in regenerative cities. [Conclusion] The TONED in resource-based cities exhibited significant regional disparities and spatial clustering effects, influenced by a combination of internal and external factors. Therefore, resource-based cities should balance differentiated construction and integrated development, focus on green transition, and fully leverage the leading role of new economic factors.